Sistem Informasi Rekam Medis Klinik Berbasis Manajemen Arsip Medis Menggunakan Kodifikasi Warna Huffman - Migunani; Yanu Putranto (Jurnal Manajemen Informatika & Teknologi, 2021)
Medical record is a file containing records and documents regarding patient identity, examination, treatment, actions and other services that have been provided to patients in health care facilities. The problem that occurs at the Main Clinic of Meditama Semarang is the management of medical data or archives that are less effective and efficient. There was an error in recording the patient's identity, doubling the medical record number, the patient data not being up-to-date, writing the wrong diagnosis with the examining doctor. The medical record information system with Huffman codification is designed with the aim of managing medical record data so that it can run properly, quickly and effectively. The system development method uses SDLC (system development life cycle) by making UML diagrams such as use case diagrams, class diagrams, activity diagrams, entity relationship diagrams as the system design stage. This information system is WEB-based using a web-based programming language supported by a database. The results of this system design are expected to be one solution to the problems that have occurred so far.Keywords: Information System, Medical Record, SDLC, WEB-Based